How Do Profitability and Tax Avoidance Influence Enterprise Value in the Food and Beverages Sub-Sector? - Nadya Eka Putri; Sari Rusmita (Poltanesa, 2025)
Every company aspires to increase its value through business activities to achieve its goals. Enterprise or firm value is a crucial determinant of a company's overall well-being for investors. Profitability and tax avoidance are some of the many factors that determine this value. This research uses a quantitative method that studies manufacturing companies of the food and beverages sub-sector listed on the Indonesia Stock Exchange (IDX) from 2017 to 2020 as samples. The findings of this study show that profitability, indicated by return on assets (ROA), affects enterprise value, where t-value > t-table (14.156 > 1.674) with a significance of 0.000 > 0.05, so it is concluded that profitability has a positive significant influence on enterprise value. Similarly, Tax Avoidance, measured with effective tax rate (ETR), affects enterprise value, where t-value > t-table (3.901 > 1.674) with a significance of 0.000 > 0.05, so it is deduced that Tax Avoidance has a positive significant influence on enterprise value.